The Curies' element: state of the art and perspectives on the use of radium in nuclear medicine - Sara Franchi; Mattia Asti; Valerio Di Marco; Marianna Tosato (SpringerOpen, 2023)
Abstract Background The alpha-emitter radium-223 (223Ra) is presently used in nuclear medicine for the palliative treatment of bone metastases from castration-resistant prostate cancer. This application arises from its advantageous decay properties and its intrinsic ability to accumulate in regions of high bone turnover when injected as a simple chloride salt. The commercial availability of [223Ra]RaCl2 as a registered drug (Xofigo®) is a further additional asset. Main body The prospect of extending the utility of 223Ra to targeted α-therapy of non-osseous cancers has garnered significant interest. Different methods, such as the use of bifunctional chelators and nanoparticles, have been explored to incorporate 223Ra in proper carriers designed to precisely target tumor sites. Nevertheless, the search for a suitable scaffold remains an ongoing challenge, impeding the diffusion of 223Ra-based radiopharmaceuticals. Conclusion This review offers a comprehensive overview of the current role of radium radioisotopes in nuclear medicine, with a specific focus on 223Ra. It also critically examines the endeavors conducted so far to develop constructs capable of incorporating 223Ra into cancer-targeting drugs. Particular emphasis is given to the chemical aspects aimed at providing molecular scaffolds for the bifunctional chelator approach.